2014
DOI: 10.1007/s00246-014-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of the Ascending Aorta in Conotruncal Heart Defects

Abstract: Dilatation of the ascending aorta is an important sequel in conotruncal anomalies, such as tetralogy of Fallot (TOF) or d-transposition of the great arteries (TGA). We measured dimensions and their progression at different levels of the ascending aorta in 80 patients. In TOF patients, mean z-score for aortic annulus was 1.65 (range -3.16-6.47), for sinus 1.93 (range -2.28-5.39), for st-junction 4.15 (range 0.0-8.18), and for ascending aorta 3.51 (range -1.23-6.36). Over time, annulus z-scores increased in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Increased aortic pressure leads to aortic dilation gradually. The increase in systemic resistance is not a result of vascular resistance alteration but of the increase in blood viscosity [14][15][16][17]. Although higher Hb aggravates the risk of aortic dilation and systemic stroke, it is also helpful in reducing right to left shunt and promoting an increase in pulmonary blood flow in TOF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased aortic pressure leads to aortic dilation gradually. The increase in systemic resistance is not a result of vascular resistance alteration but of the increase in blood viscosity [14][15][16][17]. Although higher Hb aggravates the risk of aortic dilation and systemic stroke, it is also helpful in reducing right to left shunt and promoting an increase in pulmonary blood flow in TOF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the fate of the aorta and AV in patients with repaired congenital heart disease including conotruncal anomalies, and the majority of them focused on the aortic root and ascending aorta in those who have reached adult age. [16][17][18][19][20]25 To our knowledge, this report is the first that focuses on patients with conotruncal anomalies who received AVR during childhood to provide reliable information about long-term transplant-free survival for a relatively large cohort that can't be gathered from any single institution. Unlike previously published reports that described aortic reoperations mainly for aortic root pathology, the indication for surgery in our series was AV disease that was present in all the children in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Moreover, children with other forms of conotruncal anomalies such as tetralogy of Fallot (TOF), pulmonary atresia with ventricular septal defect (PAVSD), and double outlet right ventricle (DORV) can develop aortopathy ± AV disease that occasionally requires intervention. [17][18][19][20][21] Although the majority of these children can usually be managed medically, AV repair or replacement (AVR) is occasionally needed. In these patients with conotruncal anomalies, AVR is usually needed at older age as adolescents or adults; however, earlier intervention might be necessary, posing surgical and management hurdles given the challenges in performing AVR in small children.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have performed longitudinal measurements to demonstrate if the AD found in CTD is likely to progress over time. In one study of children with both TOF and TGA, independent predictors of a longitudinal increase in Z -scores of the ascending aorta included male sex and presence of aortic regurgitation ( 30 ). A study of adults with repaired tetralogy, utilizing MRI as the imaging technique, showed minimal growth in TOF over the course of 3 years, with a very small number of aortas increasing in size from below to above a threshold value of 5 cm ( 31 ).…”
Section: Possible Mechanisms For Aortic Root Dilation In Conotruncal mentioning
confidence: 99%